Utilization of Symbolic Interactionism, Pragmatism, and Social Constructionism in Development Communication Campaigns in Nigeria - Udoudom, Uduak; Ekpe, Patrick; George, Kufre (International Journal of Multidisciplinary Approach Research and Science, 2024)
This qualitative case study analysed the utilization of symbolic interactionism, pragmatism, and social constructionism in recent development communication campaigns in Nigeria. A dataset of 87 campaigns over the last 5 years across rural, urban, northern, southern, and coastal regions was compiled. Deductive and inductive thematic analysis examined shared meanings, communicative actions towards desired ends, socially constructed representations, and additional context-specific patterns. These theoretical lenses provide valuable insights into target audiences, messaging techniques, and facilitating behavioural and social change. Symbolic interactionism focuses on shared meanings arising through social interactions and informs the cultural framing of campaign messages. Pragmatism suggests appealing to the practical impacts on people’s lives rather than abstract principles to motivate change. Finally, social constructionism sees societal issues as constructed through discourse, which campaigns can influence through strategic communication. Together, these three perspectives offer a conceptual toolkit for designing resonant campaigns, grounded in the local context, that raise awareness on issues like poverty, health, and gender equality while also shaping public discourse and norms in the longer term. Further scholarship on practical applications of these theories can improve developmental outcomes in Nigeria. This desk analysis provides a foundation for future empirical studies on campaign design and reception, and sets an agenda for theory-driven communication strategies that create meaningful social change.